Effect of nicotinic stimulation of the amygdaloid complex on water and sodium chloride intake - Saad, W. A. [UNESP]; Bengtson, R. M. [UNESP]; Camargo, L. A A [UNESP]; Menani, José Vanderlei [UNESP]; Renzi, Antonio [UNESP]; Luiz, A. C. [UNESP] (My University, 1994)
We studied the nicotine stimulation of the amygdaloid complex (AMG) on sodium and water intake in satiated and water-deprived rats. Nicotine produced no change in sodium or water intake in satiated animals when injected directly into the AMG. In water-deprived animals, nicotine injected into the AMG (basolateral nuclei) only blocked sodium chloride intake. We have previously demontrated that carbachol inhibits water and sodium intake in both satiated and water-deprived animals injected into the AMG. Injection of hexamethonium into the AMG totally blocked water intake in satiated and water-deprived animals. Hexamethonium injected into the AMG prior to nicotine produced no change in sodium intake. Thus, the present data suggest that sodium and water intake are mediated by a specific population of cholinoceptive neurons in the amygdaloid complex.
Keywords: amygdaloid complex; hexamethonium; nicotine; sodium appetite; water intake; carbachol; amygdaloid nucleus; animal experiment; cholinergic system; controlled study; drug effect; fluid intake; intracerebroventricular drug administration; male; nonhuman; rat; sodium intake